Influences of acute alcohol consumption, sexual precedence, and relationship motivation on women's relationship and sex appraisals and unprotected sex intentions. (March 2015) - Jacques-Tiura, Angela J.; Norris, Jeanette; Kiekel, Preston A.; Davis, Kelly Cue; Zawacki, Tina; Morrison, Diane M.; George, William H.; Abdallah, Devon Alisa
Guided by the cognitive mediation model of sexual decision making (Norris, Masters, & Zawacki, 2004 . Cognitive mediation of women's sexual decision making: The influence of alcohol, contextual factors, and background variables. Annual Review of Sex Research, 15, 258–296), we examined female social drinkers' ( N = 162) in-the-moment risky sexual decision making by testing how individual differences (relationship motivation) and situational factors (alcohol consumption and sexual precedence conditions) influenced cognitive appraisals and sexual outcomes in a hypothetical sexual scenario. In a path model, acute intoxication, sexual precedence, and relationship motivation interactively predicted primary relationship appraisals and independently predicted primary sex appraisals. Primary appraisals predicted secondary appraisals related to relationship and unprotected sex, which predicted unprotected sex intentions. Sexual precedence directly increased unprotected sex intentions. Findings support the cognitive mediation model and suggest that sexual risk reduction interventions should address alcohol, relationship, sexual, and cognitive factors.